THE COMPLEX OF EMOTIONAL EXPERIENCES, RELEVANT MANIFESTATIONS OF INSPIRATION - Pavel A. Starikov; Eugenia P. Porkhacheva; Svetlana N. Lykova (Образование и наука)
The aim of the study is to investigate structure of emotional experiences, relevant manifestations of inspiration creative activities of students.Methods. The proposed methods of mathematical statistics (correlation analysis, factor analysis, multidimensional scaling) are applied.Results and scientific novelty. The use of factor analysis, multidimensional scaling allowed to reveal a consistent set of positive experiences of the students, the relevant experience of inspiration in creative activities. «Operational» rueful feelings dedicated by M. Chiksentmihaji («feeling of full involvement, and dilution in what you do», «feeling of concentration, perfect clarity of purpose, complete control and a feeling of total immersion in a job that does not require special efforts») and experiences of the «spiritual» nature, more appropriate to peaks experiences of A. Maslow («feeling of love for all existing, all life»; «a deep sense of self importance, the inner feeling of approval of self»; «feeling of unity with the whole world»; «acute perception of the beauty of the world of nature, “beautiful instant”»; «feeling of lightness, flowing») are included in this complex in accordance with the study results. The interrelation of degree of expressiveness of the given complex of experiences with inspiration experience is considered.Practical significance. The results of the study show structure of emotional experiences, relevant manifestations of inspiration. Research materials can be useful both to psychologists, and experts in the field of pedagogy of creative activity.